2020
DOI: 10.1177/0022242920912732
|View full text |Cite
|
Sign up to set email alerts
|

Full Disclosure: How Smartphones Enhance Consumer Self-Disclosure

Abstract: Results from three large-scale field studies and two controlled experiments show that consumers tend to be more self-disclosing when generating content on their smartphone versus personal computer. This tendency is found in a wide range of domains including social media posts, online restaurant reviews, open-ended survey responses, and compliance with requests for personal information in web advertisements. The authors show that this increased willingness to self-disclose on one’s smartphone arises from the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 56 publications
(77 reference statements)
1
74
0
1
Order By: Relevance
“…It also raises the question of what to expect from advertising creativity in contexts where consumers are unlikely to pay attention to and process ads, such as digital and mobile media. The meta-analysis did not include any such studies, but the results suggest that effects should be weaker in media such as smartphones where focus is very directed at other focal tasks (Melumad and Meyer 2020). At the same time, effects should be stronger for advertising content in own channels and in media where consumers voluntarily seek out advertising (Rosengren and Dahlen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It also raises the question of what to expect from advertising creativity in contexts where consumers are unlikely to pay attention to and process ads, such as digital and mobile media. The meta-analysis did not include any such studies, but the results suggest that effects should be weaker in media such as smartphones where focus is very directed at other focal tasks (Melumad and Meyer 2020). At the same time, effects should be stronger for advertising content in own channels and in media where consumers voluntarily seek out advertising (Rosengren and Dahlen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the number of smartphone users worldwide has more than doubled during this interval [83]. Additionally, people have developed strong bonds to them, although this is less likely to explain our results since in our studies, participants were exposed to a lab device [77,84,85]. If any of these conjectures were true, then our findings would provide an updated assessment of the social consequences of the mere presence of a mobile phone, suggesting that its effect was short-lived.…”
Section: Non-replication Of Przybylski and Weinstein (2013)mentioning
confidence: 95%
“…For example, crowded environments lead to a loss of perceived control, which could decrease willingness to provide data. Concerns about exploitation may also differ on the basis of the device used to interact with AI (RQA9), as research has shown that consumers are more likely to self-disclose when using smartphones versus PCs (Melumad and Meyer 2020).…”
Section: The Ai Data Capture Experiencementioning
confidence: 99%